Pyogenıc granuloma treated with topical timolol in a 7-month-old child. - Atakan, M.; Atakan, T.G.; Ulusoy, M.O.; Ayanoğlu, B.T. (European Journal of Pediatric Dermatology, 2016)
Pyogenic granuloma (PG) is a vascular nodule of the skin and oral mucosa; it is considered an exaggerated angiogenic response to minor trauma. PG usually is painless and bleeds easily. It can be treated with medical therapy or with surgical methods like excision, curettage or laser treatments. The effects of beta-blockers on endothelial growth are variable, probably due to their anti-angiogenic, pro-apoptotic, and vasoconstrictive properties. Here we report a 7 month old infant with a pyogenic granuloma on his philtrum (upper lip) treated with topical timolol 0.5% gel for 4 months and completely healed after treatment.